Genetic divergence in tomato lines (Solanum lycopersicum L.) (Journal of the Bangladesh Agricultural University, 2016)
Twenty genotypes of tomato were assessed for their genetic divergence using Mahalanobis D2statistics. Based on D2 values of eleven yield related characters, genotypes were grouped in to five clusters. Maximum genotypes were grouped in cluster II (6) followed by cluster IV (5) the remaining 9 genotypes were distributed in three clusters, four in cluster III, three in cluster I and two genotypes in cluster V. Clustering pattern indicated that there was no association between geographical distribution of genotypes and genetic divergence. The mean intra and inter cluster distance (D) revealed that cluster I had highest intra cluster distance (0.979), while the inter cluster distance was maximum between cluster III and I (13.546) followed by III and V (11.218). The characters like plant height, fruit weight, fruits per plant contributed maximum to genetic divergence.J. Bangladesh Agril. Univ. 13(1): 61-64, June 2015